The impact of the introduction of a colposcopy service in a rural sub-district on the uptake of colposcopy - Blanckenberg, Natasha (Stellenbosch : University of Stellenbosch, 2015)
Objectives: To describe the establishment of a colposcopy service in a district hospital in a rural sub-district and to assess its impact on the uptake of colposcopy. Design: A retrospective double group cohort study using a laboratory database of cervical cytology results, clinical records and colposcopy clinic registers. Setting: The Overstrand sub-district in the Western Cape: 80 000 people served by 7 clinics and a district hospital in Hermanus, 120 km from its referral hospitals in Cape Town and Worcester. A colposcopy service was established at Hermanus Hospital in 2008. Subjects: All women in the Overstrand sub-district who required colposcopy on the basis of cervical smears done in 2007 and 2009. Outcome measures: The number of women booked for colposcopy at distant referral hospitals in 2007 and at the district hospital is 2009, the proportion of those women who attended colposcopy, the time from cervical smear to colposcopy, comparison between the two years. Results: The uptake of colposcopy booked for distant referral hospitals was 67% in 2007. The uptake improved by 18% to 79% for the local district hospital colposcopy service in 2009 (p=0.06). When analysed excluding patients from an area with no transport to the district hospital, the improvement was more marked at 22% (p=0.02). The delay from cervical smear to colposcopy improved significantly from 170 to 141 days (p=0.02). Conclusion: The establishment of a colposcopy service in a rural sub-district increased the uptake of colposcopy and decreased the delay from cervical smear to colposcopy. This district hospital colposcopy service removed 202 booked patients in one year from the colposcopy load of its referral hospitals.